Computerized Simulation Education on Physiotherapy Students' Skills and Knowledge: A Systematic Review. - Rezayi, Sorayya; Shahmoradi, Leila; Ghotbi, Nastaran; Choobsaz, Haniyeh; Yousefi, Mohaddeseh Hafez; Pourazadi, Shahab; Ardali, Zakiyeh Raisi (BioMed Research International, 2022)
Introduction. Applying computerized simulation education tool for learning in medical domains is widely used in many countries. This review is aimed at systematically investigating the computerized simulation tools developed to educate physiotherapy students and determine the effectiveness of these interventions. Methods. A comprehensive search was conducted in Medline (through PubMed) and Scopus databases from inception to Sept. 10, 2022. The studies that examined the effectiveness of computerized simulation-based interventions were included. Results. Sixteen studies were included in this systematic review. All included examinations were ranked "good" or "low risk of bias" based on the criteria utilized in the Joanna Briggs Institute (JBI) scale and the Effective Public Health Practice Project (EPHPP) tool. Most of the articles (43%) were conducted in the USA and 25% in Australia. In 43% of the total studies, the study population was only physiotherapy students, and in 12.5% of them, the scope of education was related to practical skills training. Three of the 16 reviewed articles presented positive qualitative results; thirteen quantitative investigations also declared statistically positive effects. Positive effects have been seen in areas such as improving professional and behavioral abilities, improving knowledge and self-confidence, and reducing stress. The sample size of the studies ranged from eight to 162 participants. The limited sample sizes in groups, lack of interaction, and short follow-up duration were the most consistent limitations evident within the included studies. Conclusion. Computerized simulation education approaches can help to improve physiotherapy students' skills and knowledge. They also have great potential to reduce learning costs and increase the quality of education.